Social Construction Of The Patient's And Psychologist's Image: Implicit Premises' Function (Journal of Namibian Studies : History Politics Culture, 2023)
These days, international aid agencies and non-governmental organizations are promoting awareness campaigns, policies, and practices that give people's mental health more attention. Major players in mental health are psychologists and patients, whose perceptions are socially constructed. However, many people are still unsure of what a psychologist does or who "psychologists" and "patients" are. This confusion might highlight stigma and stereotypes surrounding mental health in general. Thus, taking on the concepts of "psychologist" and "patient" head-on could be a small step toward dispelling myths and bringing order to the mental health landscape. The implicit contextual premises that form specific framings around which the patient's and psychologist's images are socially and culturally co- constructed are the main focus of our study. To achieve this, we have examined the discourses and various perspectives that underlie the social image of the patient and the psychologist from a variety of sources or contextual domains, including online psychology forums, university websites, and an online survey. We have identified every point of view and argument pertaining to the different conceptions of the patient and the psychologist from a methodological standpoint and in accordance with the pragmatic-dialectical approach. Using the Argumentum Model of Topics, we have clarified the implicit premises underlying each argumentative inference. We have recreated the various framings involved in the various contextual domains based on these analyses. The results demonstrate how powerful implicit contextual premises are in creating stigmatization in laypeople's perceptions of the patient and the psychologist. Specifically, we have found that institutional premises predominate over individual ones in contextual domains that are more defined; in contrast, heterogeneous individual premises are more prevalent in informal contextual domains. Our study emphasizes that the only way we can alter subjacent contextual premises at the heart of stigma and the stereotypical world's images is by replacing outdated implicit premises with brand-new, unimagined ones.